2021
DOI: 10.1007/s13311-021-01129-z
|View full text |Cite|
|
Sign up to set email alerts
|

Thymectomy and Risk of Generalization in Patients with Ocular Myasthenia Gravis: A Multicenter Retrospective Cohort Study

Abstract: This study aims to investigate the association between thymectomy and the risk of generalization in patients with ocular myasthenia gravis (MG). Data on patients with ocular MG from seven neurological centers in China were retrospectively reviewed. Ocular MG naïve to immunotherapy was categorized according to whether thymectomy was performed (thymectomized group vs. nonsurgical group). Patients in the thymectomized group all underwent surgery within 2 years since ocular symptom onset. The main outcome measure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 41 publications
2
18
0
Order By: Relevance
“…Consistent with previous studies, our data indicated that the presence of thymoma has been identified as a risk factor for the generalization of OMG [10,21]. Moreover, some researchers have investigated the encouraging role of thymectomy in reducing the risk of generalization [13,22]. However, thymectomy was excluded as a potential predictor by multiple Cox regression analysis in the present study.…”
Section: Discussionsupporting
confidence: 90%
“…Consistent with previous studies, our data indicated that the presence of thymoma has been identified as a risk factor for the generalization of OMG [10,21]. Moreover, some researchers have investigated the encouraging role of thymectomy in reducing the risk of generalization [13,22]. However, thymectomy was excluded as a potential predictor by multiple Cox regression analysis in the present study.…”
Section: Discussionsupporting
confidence: 90%
“…It was claimed that the patients who develop GMG very early may be different from other patients with OMG. Several studies also followed the criterion of Oosterhuis ( 10 , 19 , 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, preventing progression from ocular MG to generalized MG is crucial. In this regard, several studies have reported that early immunotherapy and thymectomy reduced the risk of generalization (4)(5)(6)(7)(8)(9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies reported that early thymectomy in OMG patients was associated with lower generalization than in patients without thymectomy [20][21][22]. Recently, we reported that thymectomy significantly reduced the generalization risk in OMG patients with and without thymoma or hyperplasia [23]. To reduce the influence of this strong confounding factor to the largest extent, we adopted the IPTW approach and adjusted thymectomy in the multivariable Cox regression model.…”
Section: Discussionmentioning
confidence: 99%